2007
DOI: 10.21273/hortsci.42.5.1192
|View full text |Cite
|
Sign up to set email alerts
|

Preharvest Applications of Sprayable 1-methylcyclopropene in the Orchard for Management of Apple Harvest and Postharvest Condition

Abstract: A sprayable formulation of 1-methylcyclopropene (1-MCP; AgroFresh, Spring House, PA) was applied to ‘Scarletspur Delicious’ and ‘Cameo’ apples in the orchard 1 to 3 weeks before harvest and compared in different postharvest studies with the commercial postharvest 1-MCP fruit treatment (SmartFresh; AgroFresh) and with aminoethoxyvinylglycine (AVG; ReTain; Valent BioSciences, Walnut Creek, CA). Treated apples were held in air storage for 50 to 60 d or in controlled-atmosphere storage for 120 to 125 or 21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
43
2
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 17 publications
(20 reference statements)
5
43
2
2
Order By: Relevance
“…Commercial formulations of 1‐methylcyclopropene (1‐MCP) have facilitated broader agricultural applications of the ethylene‐action inhibitor, particularly in post‐harvest settings (Elfving et al . ). 1‐MCP treatment reduced chilling injury symptoms of loquat (Cao et al .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Commercial formulations of 1‐methylcyclopropene (1‐MCP) have facilitated broader agricultural applications of the ethylene‐action inhibitor, particularly in post‐harvest settings (Elfving et al . ). 1‐MCP treatment reduced chilling injury symptoms of loquat (Cao et al .…”
Section: Introductionmentioning
confidence: 97%
“…Ethylene production correlated closely with DNA and nuclear fragmentation in hybrid seedlings from the cross Nicotiana suaveolens × N. tabacum, indicating that ethylene is an essential factor mediating PCD (Yamada and Marubashi 2003). Commercial formulations of 1-methylcyclopropene (1-MCP) have facilitated broader agricultural applications of the ethylene-action inhibitor, particularly in postharvest settings (Elfving et al 2007). 1-MCP treatment reduced chilling injury symptoms of loquat (Cao et al 2009), green bean (Cho et al 2008) and persimmon fruit (Salvador et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…3) in the absence of 'significant' ethylene or changes thereof. However, starch hydrolysis can be slowed by treatment of fruit on the tree with aminoethoxyvinylglycine (ReTain, Valent Biosciences) and 1-methylcyclopropene (Harvista, AgroFresh, Inc.), inhibitors of ethylene production and perception, respectively (Elfving et al, 2007;Watkins et al, 2010 Yuan andCarbaugh, 2007). Johnston et al (2009) found that some maturity parameters such as starch are very ethylene sensitive, and therefore, even very low amounts of IEC may cause the onset of starch hydrolysis.…”
Section: Discussionmentioning
confidence: 99%
“…However, starch hydrolysis can be slowed by treatment of fruit on the tree with aminoethoxyvinylglycine (ReTain, Valent Biosciences) and 1-methylcyclopropene (Harvista, AgroFresh, Inc.), inhibitors of ethylene production and perception, respectively (Elfving et al, 2007;Watkins et al, 2010;Yuan and Carbaugh, 2007). Johnston et al (2009) found that some maturity parameters such as starch are very ethylene sensitive, and therefore, even very low amounts of IEC may cause the onset of starch hydrolysis.…”
Section: Discussionmentioning
confidence: 99%